A REVIEW OF SYN-GAS POLYGENERATION AS ONE OF SOLUTIONS TO SOLVE NATIONAL ENERGY CRISIS - NURHADI NURHADI; NINING S. NINGRUM (Puslitbang tekMIRA, 2006)
In the future, Indonesian crisis energy can be overcome by the use of coal as oil substitute. Substi- tuting oil by coal is still a problem due to unfamiliar using coal by Indonesian, inappropriate technology selection and environmental pollution. The use of coal-based syn-gas as various energy resources and chemical material can be conducted in an integrated system called syn-gas polygeneration. Syn- gas polygeneration is efficient and environmental friendly. Its process can be conducted gradually. Yet government policy is needed to start applying syn-gas polygeneration from coal gasification.